Peran Kepemimpinan Kiai dalam Meningkatkan Motivasi Kerja Dosen Ma’had Aly Sukorejo Situbondo - Wawan Juandi; Juwairiyah Juwairiyah (Jurnal Pendidikan Islam Indonesia, 2019)
The figure of a Kiai as the director of Ma'had Aly Sukorejo Situbondo is very crucial in motivating lecturers’ work.This research aims to find and to analyze the role and the strategies of Kiai in enhancing the lecturers’ work motivation. It uses a qualitative approach that emphasizes inductive analysis through reduction, presentation, and conclusion. The role of Kiai's leadership in enhancing lecturers’ work motivation at Ma'had Aly Sukorejo Situbondo is in his capacity as a competitive supervisor in every lecturer’s ability to increase personal awareness so can do work based on main duties and functions (TUPOKSI), by giving an example and spiritual guidance before instructing. The Kiai's strategy as the director of Ma'had Aly are holds a meeting with masyayikh, maintain sustainable control to Ma'had Aly 's regulation, buildsan adjacency with all elements (egalitarian), uses uswatun hasanah approach and Sufistic strategies, discipline in carrying out the duties. The positive impact of the strategies of Kiai in enhancing the lecturers’ work motivation at Ma'had Aly Sukorejo is the lecturers respect him more, dare to express their aspirations, but still maintain politeness.